# Solve 5x - 2= 3x + 7

• 613 views

1 - First we need to get all the x values on one side and all the numbers on the otherside of the equals sign.

2 - We then need simplify the equation to get 1 x.

Solve 5x - 2= 3x + 7

1 - Remember, whatever you do to one side of the equation, you must do to the otherside of the equation. We want to get rid of the -2. In order to do this we can add 2. This is because -2 + 2 = 0.

5x - 2= 3x + 7

ADD 2                  (5x - 2 + 2 = 3x + 7 +2)

5x = 3x +9

Now we need to get the x's on the same side, let's say the left hand side. In order to do this, we subtract 3x.

5x = 3x +9

SUBTRACT 3x            (5x - 3x = 3x - 3x + 9)

2x = 9

2 - We now have the x's on one side and the numbers on the other. We next need to simplify so we can get x on its own. To do this we can divide by 2 because 2x/2 = x

2x = 9

DIVIDE BY 2             (2x/2 = 9/2)

x = 4.5

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this.